Transformational leadership of educational directives and commitments - Carranza-Villón, Mayra I. (2020)
The present research work was carried out with the objective of demonstrating the relationship between the transformational leadership of the directors and the commitments of the teachers of the Teniente Fiscal Education Unit Hugo Ortiz, Guayaquil-Ecuador. It is an investigation of basic type, descriptive level and assumes the correlational design. The population and sample consisted of 212 members of the mentioned institution. The technique used was the survey and the instrument the structured questionnaire to measure both study variables that consisted of 35 items; with an amplitude of Likert scale (always, almost always, sometimes, almost never and never); The other measuring instrument consisted of 27 items, the instruments have been validated through expert judgment and have an adequate level of reliability: 0.870 and 0.858 respectively. To measure the correlation, the Pearson ratio coefficient was used, in which it is observed that there is a correlation of 0.752, with a significant relationship between the transformational leadership of the managers and the commitments of the teachers in the studied population. Therefore, it is concluded with a 95% confidence level that there is a significant relationship between both variables.